Pengaruh Keseimbangan Kehidupan Kerja Dan Resiliensi Terhadap Produktivitas Kerja Karyawan Pada Koperasi Simpan Pinjam Mitra Niaga Mamuju - Khatimah, Husnul; Aqil, Muhammad; Mappigau, Ernawaty; Sudirman, Sudirman (Journal of Management Branding, 2024)
This research was conducted with the aim of finding out the influence of work-life balance and resilience on employee work productivity at the Mitra Niaga Mamuju Savings and Loans Cooperative. This research uses quantitative methods, the research sample uses a total sampling technique with a total of 32 respondents. Data collection was carried out by observation, interviews, and distributing questionnaires in the form of instruments directly to respondents. Testing the quality of research instruments uses validity tests and reliability tests. The analytical tool used is multiple linear regression analysis, then hypothesis testing uses partial tests (t test), simultaneous tests (F test), and to determine the contribution of the independent variable to the dependent variable using the coefficient of determination. The research results obtained were (1) Work-life balance has a significant effect on work productivity; (2) Resilience has a significant effect on work productivity; (3) Work-life balance and resilience have a significant influence simultaneously on employee work productivity. Meanwhile, the contribution of work-life balance and resilience to employee work productivity is classified as moderate with a percentage of 56.3%, which means there are still 43.7% other factors that can influence employee work productivity at the Mitra Niaga Mamuju Savings and Loans Cooperative